2017
DOI: 10.4236/ojog.2017.72026
|View full text |Cite
|
Sign up to set email alerts
|

Vesicocutaneous Fistula: A Rare Complication of Pelvic Trauma

Abstract: Background: Vesicocutaneous fistula is a rare type of urinary fistula. It is often distressing and may negatively impact on the quality of life of an affected person. Our aim in this case report is to document a case of vesicocutaneous fistula following pelvic trauma from road traffic accident and share our experience in the management of this condition. Case Report: We report the case of a 30 year-old primipara who had urinary incontinence following pelvic trauma sustained from road traffic accident. Examinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
0
0
Order By: Relevance
“…Management depends on the presenting symptoms, the complexity of the fistula and the underlying cause [14]. Urinary diversion to reduce the hydrostatic pressure of the bladder is vital therefore urethral catheter was kept for 21 days in our case.…”
Section: Discussionmentioning
confidence: 90%
“…Management depends on the presenting symptoms, the complexity of the fistula and the underlying cause [14]. Urinary diversion to reduce the hydrostatic pressure of the bladder is vital therefore urethral catheter was kept for 21 days in our case.…”
Section: Discussionmentioning
confidence: 90%
“…The location of the fistula and the amount of output determine the extent of electrolyte loss. As research has highlighted [2,3], swift correction of any identified derangements is imperative.…”
Section: Introductionmentioning
confidence: 99%